Dermatomyositis/polymyositis and anti-TNF-α therapies: a literature review. (October 2013) - Brunasso, Alexandra MG; Aberer, Werner; Massone, Cesare
Dermatomyositis (DM) is an idiopathic inflammatory myopathy, which is potentially life threatening. To achieve disease remission, different therapeutic schedules may be required, with corticosteroid regimen being the first-line treatment. Recently the role of anti-TNF-α therapies as potential steroid sparing agents has been postulated. Herein, we performed a systematic review of the literature with special focus on anti-TNF-α therapies and DM. Different case reports, case series and one randomized controlled trial support the use of anti-TNF-α blocking agents, in particular etanercept and infliximab, as adjuvant therapy for DM and polymyositis (PM). The only available randomized controlled trial reported successful treatment with etanercept in 5/11 patients that weaned off prednisone in contrast to all five patients on the placebo group that failed the prednisone withdrawal schedule. There are approximately 42 other cases reported regarding the use of anti-TNF-α agents in patients affected by DM or PM. In 12 (28.6%) of those cases, a worsening of the disease was reported and in 13 patients (31%) the onset of severe adverse events forced the withdrawal of the drug, including two fatal cases. Another noteworthy fact regards the paradoxical onset of DM or PM in patients treated with TNF-α antagonists (18 cases reported), mainly for rheumatoid arthritis (15 cases). There is insufficient evidence from available reports to justify the routine use of anti-TNF-α agents in the management of patients affected by DM or PM. Further studies should be conducted before we can systematically use anti-TNF-α agents in the management of DM.